Defining the Functional Role of NaV1.7 in Human Nociception - McDermott, L; Weir, G; Themistocleous, A; Segerdahl, A; Blesneac, I; Baskozos, G; Clark, A; Millar, V; Peck, L; Ebner, D; Tracey, I; Serra, J; et al. (Elsevier, 2019)
Loss-of-function mutations in NaV1.7 cause congenital insensitivity to pain (CIP); this voltage-gated sodium channel is therefore a key target for analgesic drug development. Utilizing a multi-modal approach, we investigated how NaV1.7 mutations lead to human pain insensitivity. Skin biopsy and microneurography revealed an absence of C-fiber nociceptors in CIP patients, reflected in a reduced cortical response to capsaicin on fMRI. Epitope tagging of endogenous NaV1.7 revealed the channel to be localized at the soma membrane, axon, axon terminals, and the nodes of Ranvier of induced pluripotent stem cell (iPSC) nociceptors. CIP patient-derived iPSC nociceptors exhibited an inability to properly respond to depolarizing stimuli, demonstrating that NaV1.7 is a key regulator of excitability. Using this iPSC nociceptor platform, we found that some NaV1.7 blockers undergoing clinical trials lack specificity. CIP, therefore, arises due to a profound loss of functional nociceptors, which is more pronounced than that reported in rodent models, or likely achievable following acute pharmacological blockade.